The Impact of the Covid-19 Pandemic on the Primary Real Estate Market in Poland in 2019-2021 - Analysis of the Current Situation - Marta MARTYNIAK (Communications of International Proceedings, 2021)
This article attempts to assess the impact of the COVID-19 pandemic on the development industry in the period 2019-2021 and presents current analysis of the situation on the primary real estate market. The aim of the study was to assess the resilience of this segment of the economy to the macroeconomic shock caused by the outbreak of SARS-CoV-2 in Poland, including the developer’s response to the effects of the pandemic and government COVID restrictions. The article describes the behavior and problems of development companies with which they struggle during a pandemic, including their feelings about the new economic reality. Based on the obtained research material - industry research reports and Statistics Poland (GUS) data - a synthetic analysis of data reflecting the current state of the development market was performed. The analysis covered, among others, data on average offer prices on the primary market, the number of completed properties, issued construction permits or financial results achieved by developers in relation to the course of the pandemic in Poland. The obtained results allow us to conclude that this industry, despite the initial difficulties, copes quite well with the new economic reality and the negative effects of the pandemic, and therefore shows a certain resistance to macroeconomic shocks. Moreover, the achieved research results provide new, up-to-date information on the current situation on the primary real estate market. The article is intended for people interested in the residential real estate market in Poland, especially private investors and professional entities operating on this market.
Keywords: Residential Real Estate Market; Developer; Real Estate Development Market; COVID-19 Pandemic